Analisis Optimasi Kinerja Protokol Routing AODV dan AOMDV dengan Menggunakan Metode RFAP untuk Mencegah RREQ Flooding Attacks pada Jaringan MANET - Andy Hidayat Jatmika; I Made Windra Yudistiana; Ariyan Zubaidi (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2019)
One sector that greatly influences it is in terms of network security. This is due to the characteristics of the MANET network that are dynamic so that the MANET network is very easily disturbed by irresponsible parties. One of the attacks that can occur in MANET network is Route Request (RREQ) Flooding Attacks. In RREQ flooding attacks in the form of fake nodes that are outside the area of the network and broadcast RREQ to the destination node in the network, so that it meets the bandwidth capacity which results in a decrease in quality in determining the route of sending data or information to the destination node. To prevent the occurrence of RREQ flooding attacks, a prevention method for these attacks is required, namely the RREQ Flooding Attacks Prevention (RFAP). This method works by finding nodes that are likely to be malicious nodes then isolated from the network to be restored to normal nodes. This research will optimize the AODV and AOMDV routing protocols by adding RFAP prevention methods and knowing the performance of the two protocols in terms of throughput, average end-to-end delay and normalized routing load. Based on the results of the simulation, that the application of the method RFAP on AODV routing protocol can produce network quality is better than AOMDV protocol, both in terms of throughput, average end-to-end delay and normalized routing load.